Muhammad Qoyyim Ya'qub's Locality Expression in the Qur’any Song - Nur Anis Rochmawati (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
The practice of Islam in the archipelago is the result of the dialectic of the Shari'a text with the realities of the local culture. It can be said that Islam and culture are entities that cannot be denied each other. It became a starting point for Muhammad Qoyyim Ya'qub to interpret contextually that is integrated with aspects of locality. The song Qur'any is a form of Qoyyim's actualization of exploring and grounding the values of the Qur'an in the cultural framework of the archipelago. So, this article reveals; 1) the extent to which Muhammad Qoyyim Ya'qub reveals the locality dimension in his commentary; Song Qur’any, and 2) what strategy is used to explore the reading of the Qur'an. Paul Ricoeur's hermeneutics was used to analyze the results of Muhammad Qoyyim Ya'qub's interpretation and communication theory to map his da'wah mode. The finding explores that the Song of the Qur’an contains both appreciation and criticism. Beside internalizing, Qoyyim Ya'qub in his interpretation responds to local culture which is considered not in line with Islamic values. Lyric Poetry is the chosen medium to assist in the process of transmitting the messages of the Qur'an